Diuretic Optimization Strategies Evaluation in Acute Heart Failure - Sinclair, Heather Q. (MD Conference Express, 2010)
There is no evidence of benefit for various initial administration or dosing strategies of furosemide therapy in patients with acute decompensated heart failure. However, the high-intensification (2.5 x chronic daily oral dose) dosing strategy was associated with improvements or trends toward improvement in multiple areas. This article presents findings from the Diuretic Optimization Strategies Evaluation in Acute Heart Failure [DOSE-AHF; NCT00577135] Study.